Mutation of self-binding sites in the promoter of the MrpC transcriptional regulator leads to asynchronous Myxococcus xanthus development - McLaughlin, Maeve; Higgs, Penelope I. (Frontiers in Microbiology, 2023)
Introduction MrpC, a member of the CRP/Fnr transcription factor superfamily, is necessary to induce and control the multicellular developmental program of the bacterium, Myxococcus xanthus. During development, certain cells in the population first swarm into haystack-shaped aggregates and then differentiate into environmentally resistant spores to form mature fruiting bodies (a specialized biofilm). mrpC transcriptional regulation is controlled by negative autoregulation (NAR). Methods Wild type and mutant mrpC promoter regions were fused to a fluorescent reporter to examine effects on mrpC expression in the population and in single cells in situ. Phenotypic consequences of the mutant mrpC promoter were assayed by deep convolution neural network analysis of developmental movies, sporulation efficiency assays, and anti-MrpC immunoblot. In situ analysis of single cell MrpC levels in distinct populations were assayed with an MrpC-mNeonGreen reporter. Results Disruption of MrpC binding sites within the mrpC promoter region led to increased and broadened distribution of mrpC expression levels between individual cells in the population. Expression of mrpC from the mutant promoter led to a striking phenotype in which cells lose synchronized transition from aggregation to sporulation. Instead, some cells abruptly exit aggregation centers and remain locked in a cohesive swarming state we termed developmental swarms, while the remaining cells transition to spores inside residual fruiting bodies. In situ examination of a fluorescent reporter for MrpC levels in developmental subpopulations demonstrated cells locked in the developmental swarms contained MrpC levels that do not reach the levels observed in fruiting bodies. Discussion Increased cell-to-cell variation in mrpC expression upon disruption of MrpC binding sites within its promoter is consistent with NAR motifs functioning to reducing noise. Noise reduction may be key to synchronized transition of cells in the aggregation state to the sporulation state. We hypothesize a novel subpopulation of cells trapped as developmental swarms arise from intermediate levels of MrpC that are sufficient to promote aggregation but insufficient to trigger sporulation. Failure to transition to higher levels of MrpC necessary to induce sporulation may indicate cells in developmental swarms lack an additional positive feedback signal required to boost MrpC levels.